The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1292/jvms.70.1399
|View full text |Cite
|
Sign up to set email alerts
|

Annual Changes in Serum Leptin Concentration in the Adult Female Japanese Black Bear (Ursus thibetanus japonicus)

Abstract: ABSTRACT. In the present study, assay of the serum leptin concentration of the Japanese black bear (Ursus thibetanus japonicus) was attempted using a canine-leptin-specific sandwich enzyme-linked immunosorbent assay (ELISA). The dose-response curve of the bear serum was linear and parallel to the canine leptin standard curve. In mated and unmated bears, the serum leptin concentration was stable at low levels from May to August or September, gradually increased from September or October, and then remarkably inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Although the mechanism of puberty in bears is still not entirely clear (WHITE et al, 2005;TSUBOTA et al, 2008), it should follow some of the patterns already described for S. Reljić et al: Reproductive span in captive brown bears other species of wild mammals. In order to study the mechanism involved, it is crucial to determine the timing of the first ovulation and at the same time analyse endogenous and exogenous stimuli present.…”
Section: Introductionmentioning
confidence: 63%
“…Although the mechanism of puberty in bears is still not entirely clear (WHITE et al, 2005;TSUBOTA et al, 2008), it should follow some of the patterns already described for S. Reljić et al: Reproductive span in captive brown bears other species of wild mammals. In order to study the mechanism involved, it is crucial to determine the timing of the first ovulation and at the same time analyse endogenous and exogenous stimuli present.…”
Section: Introductionmentioning
confidence: 63%
“…The newly established canine leptin‐specific ELISA kit, which utilizes the anti‐dog leptin antibody, had been previously confirmed as useful for determining blood leptin concentrations of dogs, cats ( Felis catus ), raccoons ( Procyon lotor ), and bears ( Ursus thibetanus japonicus ) (Shibata et al, 2005; Tsubota et al, 2008). The raccoon dog is a member of Canidae and is closely related to dogs (Ward and Wurster‐Hill, '90).…”
Section: Discussionmentioning
confidence: 99%
“…The circulating leptin level is thus well correlated with body weight, and more precisely, the overall body fat content (Frederich et al, '95; Maffei et al, '95; Sagawa et al, 2002). In wild animals, various attempts have been made to use leptin as a marker for long‐term nutritional condition and body adiposity (Mustonen et al, 2005; Shibata et al, 2005; Soppela et al, 2008; Tsubota et al, 2008; Gaspar‐López et al, 2009). Annual cycles of food intake and adiposity are associated with significant seasonal changes in circulating leptin concentrations and altered leptin gene expression in the adipose tissues of some seasonal mammals, such as Siberian hamsters ( Phodopus sungorus ; Rousseau et al, 2003).…”
mentioning
confidence: 99%
“…Tøien et al (2011) documented a reduction in metabolism during hibernation to 25 % of basal rates independent of lowered body temperature, suggesting other endogenous factors may be involved in triggering the physiological changes accompanying hibernation. Studies of the processes regulating hibernation revealed a higher proportion of plasma unsaturated fatty acids during winter than during summer months, and increased leptin concentrations directly before hibernation corresponding to maximal fat content (Hissa et al 1998;Tsubota et al 2008). …”
Section: Plin2mentioning
confidence: 99%
“…Because fat serves such an important function in hibernators, it is essential to understand how fat-borne signals are utilized by the body, and conversely, how fat cells respond to metabolic cues. Two adipocyteproduced hormones, leptin and adiponectin, vary seasonally in several Ursus species with peaks occurring just prior to hibernation (Hill 2013;Hissa et al 1998;Tsubota et al 2008). However, the role of these adipokines in hibernation and in seasonal fat metabolism has yet to be firmly established.…”
Section: Introductionmentioning
confidence: 99%